Penguatan Pendidikan Islam Multikultural di Pondok Pesantren Miftahul Huda Sekardangan Blitar - Shofwan, Arif Muzayin; Farantika, Dessy; Hidayah, Choirul; Setyowati, Rina Insani (Institut Riset dan Publikasi Indonesia (IRPI), 2026)
In this era of sophisticated technology, there is indeed a demand for any educational institution to present learning that is easy to understand and quickly absorbed by students. Likewise, Islamic boarding schools are also required to use technological facilities such as laptops and projectors to provide learning to students in their environment. Without following the development of existing technology, the learning that is carried out will be far behind. This article discusses the instillation of multicultural Islamic education at the Miftahul Huda Sekardangan Blitar Islamic Boarding School. The methods used in this community service include: the lecture method, question and answer method, simulation method, and assignment method. This community service activity aims to strengthen multicultural Islamic education for students (students) through classical books that have been taught to them every day traditionally. Strengthening multicultural Islamic education through modern technology learning such as laptops, power points, and projectors is very important so that books that are taught traditionally for months or even years can be easily absorbed through these media in a short time.